SIMULATOR KENDALI PESAWAT TERBANG EXTRA 300 L BERBASIS3D DENGAN METODE SIMULATION GAME - Salam Aryanto; Nurcahyani Dewi Retnowati; Basir Basir (Institut Teknologi Dirgantara Adisutjipto, 2014)
One of the methods to improve the understanding of the learner is to use an interactive simulator aircraft by utilizing information and communication technology so as to explain the flight control system and its functions better. Making this simulator using Adobe Photoshop, 3D Studio Max, and 3DRad. The software used to create the interface design, 3D design, as well as as simulator engine. Simulator Extra 300 L aircraft provide convenience to the user to know and understand the control plane fly Extra 300 L.The use of this simulator is more interactive in the delivery of information to the user than an explanation using propsor in video form. This simulator is designed user friendly as well as trials conducted by 30 respondents, the majority of respondents stated that this simulator is good and fit for use as a medium of learning control of an aircraft.